Developmental quotient of specialist's degree students and bachelor's program students - Albert A. Abrosimov; Viacheslav V. Zayvyy (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Switching to higher education level system is the result of a significant change in terms and content of education and of its standards for evaluation. Consider research results of the educational process in terms of students development level. Research conducted on the basis of experimental data obtained by testing specialist's degree students and. It was established that all of the numerical values indicators of development for the Bachelor's program students is less than specialist's degree students. Rank correlation analysis of development indicators found that the correlation between the profile of the Bachelor's program students and specialist's degree students is statistically significant.